Vasectomy—a two year follow-up - Drury, V. W. M. (1974)
A report is given of 200 consecutive vasectomy operations performed by a general practitioner and with anaesthesia by a general practitioner. There was a bias among patients towards the upper social classes, perhaps because of better use of sources of information. The reasons for seeking vasectomy are analysed and seem to be more complex than the interviewer/operator assumed. One hundred and seventy-five couples followed up reported physical and emotional relationships to have improved in over 50 per cent of cases and to have been unchanged in virtually all the rest. An analysis of the 28 couples who were not followed up does not show any characteristics indicating a likelihood of their differing from the follow-up group.